Dielectric properties of a bisimidazolium salt with dodecyl sulfate anion doped with carbon nanotubes - Maximean, Doina Manaila; Cîrcu, Viorel; Ganea, Constantin Paul (Beilstein Journal of Nanotechnology, 2018)
A new bisimidazolium salt with dodecyl sulfate as counterion has been designed and prepared. This salt shows a SmA phase that is stable at room temperature. The new ionic liquid crystal (ILC) was characterized by 1H NMR, 13C NMR and IR spectroscopy. Its liquid crystalline properties were analyzed by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and powder X-ray diffraction (XRD) studies. The dielectric spectra of the ILC doped with different concentrations of carbon nanotubes (CNT) were recorded over a wide frequency and temperature range of 10−1 to 107 Hz and 293–338 K, respectively. The values of the activation energy were found in the range of 0.46–0.61 eV; the characteristic time was obtained by fitting the spectra of the dielectric loss with the Havriliak–Negami functions. As a result of doping the ILC with CNT, the electric conductivity increases significantly. Ionic conductivity is dominant and it was indirectly observed through the electrode polarization (EP) effect. The very high dielectric permittivity values and the decrease of the electric conductivity at low frequencies confirm the presence of EP.
Keywords: activation energy; carbon nanotubes; dielectric spectroscopy; ionic liquid crystal; relaxation time